2–10 µm Mid‐Infrared Fiber‐Based Supercontinuum Laser Source: Experiment and Simulation. Issue 6 (4th May 2020) - Venck, Sébastien; St‐Hilaire, François; Brilland, Laurent; Ghosh, Amar N.; Chahal, Radwan; Caillaud, Céline; Meneghetti, Marcello; Troles, Johann; Joulain, Franck; Cozic, Solenn; Poulain, Samuel; Huss, Guillaume; et al.
Abstract: Mid‐infrared supercontinuum (mid‐IR SC) sources in the 2–20 µm molecular fingerprint region are in high demand for a wide range of applications including optical coherence tomography, remote sensing, molecular spectroscopy, and hyperspectral imaging. Herein, mid‐IR SC generation is investigated in a cascaded silica‐ZBLAN‐chalcogenide fiber system directly pumped with a commercially available pulsed fiber laser operating in the telecommunications window at 1.55 µm. This fiber‐based system is shown to generate a flat broadband mid‐IR SC covering the entire range from 2 to 10 µm with several tens of mW of output power. This technique paves the way for low cost, practical, and robust broadband SC sources in the mid‐IR without the requirement of mid‐infrared pump sources or Thulium‐doped fiber amplifiers. A fully realistic numerical model used to simulate the nonlinear pulse propagation through the cascaded fiber system is also described and the numerical results are used to discuss the physical processes underlying the spectral broadening in the cascaded system. Finally, recommendations are provided for optimizing the current cascaded system based on the simulation results. Abstract : A cascaded silica–fluoride–chalcogenide fiber system pumped by a compact pulsed fiber laser at 1.55 µm is reported which provides a wideband supercontinuum emission spanning the entire 2–10 µm mid‐infrared range. Thus, offering a new fiber laser solution for molecular spectroscopy, remote sensing, optical coherence tomography, and hyperspectral imaging.